Calculation of hot spots for protein–protein interaction in p53/PMI‐MDM2/MDMX complexes. Issue 9 (14th December 2018) - Huang, Dading; Qi, Yifei; Song, Jianing; Zhang, John Z. H.
Abstract : The recently developed MM/GBSA_IE method is applied to computing hot and warm spots in p53/PMI‐MDM2/MDMX protein–protein interaction systems. Comparison of the calculated hot (>2 kcal/mol) and warm spots (>1 kcal/mol) in P53 and PMI proteins interacting with MDM2 and MDMX shows a good quantitative agreement with the available experimental data. Further, our calculation predicted hot spots in MDM2 and MDMX proteins in their interactions with P53 and PMI and they help elucidate the interaction mechanism underlying this important PPI system. In agreement with the experimental result, the present calculation shows that PMI has more hot and warm spots and binds stronger to MDM2/MDMX. The analysis of these hot and warm spots helps elucidate the fundamental difference in binding between P53 and PMI to the MDM2/MDMX systems. Specifically, for p53/PMI‐MDM2 systems, p53 and PMI use essentially the same residues (L54, I61, Y67, Q72, V93, H96, and I99) of MDM2 for binding. However, PMI enhanced interactions with residues L54, Y67, and Q72 of MDM2. For the p53/PMI‐MDMX system, p53 and PMI use similar residues (M53, I60, Y66, Q71, V92, and Y99) of MDMX for binding. However, PMI exploited three extra residues (M61, K93, and L98) of MDMX for enhanced binding. In addition, PMI enhanced interaction with four residues (M53, Y66, Q71, and Y99) of MDMX. These results gave quantitative explanation on why the binding affinities of PMI‐MDM2/MDMX interactions are stronger than that of p53‐MDM2/MDMX although their binding modes are similar. © 2018 Wiley Periodicals, Inc. Abstract : Predicted hot spots (ΔΔ G ≥ 2.00 kcal/mol) and warm spots (2.00 ≥ ΔΔ G ≥ 1.00 kcal/mol) of MDM2 in P53/PMI‐MDM2 interaction complexes using the MM/GBSA_IE method.